Viral hepatitis markers screen in children with Acute Lymphoblastic Leukemia Experience of Children Welfare Teaching Hospital - Al-Jadiry, Mazin F. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Patients treated for pediatric malignancy are at high risk of parenterally transmitted viral hepatitis. Objectives: To detect the seroprevalence of hepatitis B and C viral infections in children with Acute Lymphoblastic Leukemia & identify some variables that could affect its prevalence in these patients. Patients and Methods: One hundred fifty pediatric acute lymphoblastic leukemia patients, presented to Children Welfare Teaching Hospital, Baghdad, during the period from March 11th 2007 to July 31st 2007 were enrolled in this study; they were 103 males, 47 females, aged (2.25 months- 16 years). Sera of these patients were investigated for hepatitis markers including HBsAg and Anti HCV antibody. Results The majority of patients were from Baghdad 104 (69.33%). Almost all children received 3 doses of hepatitis B vaccine according to the national Iraqi vaccination schedule & 111 (74%) of them received another course of vaccination during their admission to the oncology unit at CWTH. Screening for hepatitis B virus infection was positive in 54 (36%) of cases while for hepatitis C virus infection was positive in 4 (3.25%) of cases. Conclusion Multiple blood transfusions and prolonged duration of observation of patients showed significant statistical impact on the incidence of HBV infection.